Modelling Nonlinear Preloaded Multi-Bolted Systems on the Operational State - GRZEJDA, Rafał (Engineering Transactions, 2016)
Modelling and calculations of asymmetrical multi-bolted connections at the operational stage are presented. The physical model of the joint is based on a flexible flange element that is connected with a flexible support by means of the rigid body bolt models. Between the joined elements, the nonlinear Winkler model of a contact layer is taken into consideration. A computational model of the system is proposed, which makes it possible to analyse the preloaded multi-bolted connections subjected to an eccentric normal load. The results obtained from the sample calculations are presented.